2017
DOI: 10.1007/s10826-017-0961-8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Train-The-Trainers Model for Family Peer Advocates in Children’s Mental Health

Abstract: Standardized training and credentialing is increasingly important to states and healthcare systems. Workforce shortages in children's mental health can be addressed through training and credentialing of professional peer parents (called family peer advocates or FPAs), who deliver a range of services to caregivers. A theory-based training program for FPAs targeting skills and knowledge about childhood mental health services (Parent Empowerment Program, or PEP) was developed through a partnership among a statewi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 24 publications
(41 reference statements)
1
12
0
Order By: Relevance
“…[38,39] Peer-to-peer support by parents has been used successfully to support the child mental health workforce. [40] Peer support networks (either face to face or online) help parents navigate the system and advocate for their child. [41, 42] In addition, expansion of existing support structures to assist parents to navigate the health care system e.g.…”
Section: Discussionmentioning
confidence: 99%
“…[38,39] Peer-to-peer support by parents has been used successfully to support the child mental health workforce. [40] Peer support networks (either face to face or online) help parents navigate the system and advocate for their child. [41, 42] In addition, expansion of existing support structures to assist parents to navigate the health care system e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Train-the-Trainer models involve an EBT expert providing clinical training to a community-based clinician who in turn replicates that training with other clinicians in their organization. Although this approach is widely used (e.g., Hawkins & Sinha, 1998; Rogers, Cohen, Danley, Hutchinson, & Anthony, 1986) and is considered affordable and feasible (e.g., Hoagwood et al, 2018), the effectiveness of the model is not well understood. Within behavioral health, some studies have reported a “watering down” effect from consultants to staff (Shore, Iwata, Vollmer, Lerman, & Zarcone, 1995), whereas others have reported no differences (Martino et al, 2010).…”
Section: What We Know: Training Consultation and Supervision Strategiesmentioning
confidence: 99%
“…In one example of an auxiliary model, LHWs have been trained to increase engagement in Parent-Child Interaction Therapy by addressing barriers to care and promoting home practice of skills (Barnett et al, 2016(Barnett et al, , 2019. More broadly across mental health services, the Parent Empowerment Program trains family peer advocates to work with parents to address their children's mental health needs and overcome barriers to care (Hoagwood et al, 2018;Rodriguez et al, 2011). Limited evidence has established the success of these auxiliary models.…”
Section: Auxiliary Carementioning
confidence: 99%